Taste masking of paracetamol encapsulated in chitosan-coated alginate beads - Almurisi, Samah Hamed; Doolaanea, Abd Almonem; Akkawi, Muhammad Eid; Chatterjee, Bappaditya; Sarker, Md. Zaidul Islam (Editions de Sante, 2020)
Taste masking is required for bitter drugs to enhance patient compliance, especially among the paediatric population. Paracetamol, the first line for paediatricians to treat pain and fever, is known for its bitter taste. This study aimed to mask the bitter taste of paracetamol and explore the potential of alginate microencapsulation in palatability improvement. Chitosan-coated paracetamol alginate beads were optimised using electrospray to obtain spherical beads with size below 1.5 mm. The encapsulation efficiency (EE) of the uncoated beads decreased with increased gelation time to reach 5 ± 1.32% at 60 min. Chitosan coating enhanced EE to 50–76% depending on chitosan type and concentration. EE significantly improved to 99.0 ± 1.1% by saturating the gelation bath with paracetamol. In vitro taste masking test and in vivo palatability evaluation using 12 human volunteers demonstrated that dry chitosan-coated paracetamol alginate beads were superior to the wet ones for taste masking, which was similar to the marketed paracetamol suspension and even better in aftertaste evaluation. This indicates that the microencapsulation in alginate with further chitosan coating can compensate for the usage of sweetening and flavouring agents. This helps to formulate paediatric dosage forms with minimal undesired excipients